DO DURATION OF STAY AND PARK VISITATION MATTER? AN EVALUATION OF PARK DISTANCE - Abdul Malek, Nurhayati; Nashar, Amanina (PLANNING MALAYSIA, 2020)
Among ways to keep up with healthy lifestyle include physical activities. Recent statistics by the Ministry of Health (2016) indicated a drastic increase in the prevalence of non-communicable disease from 1990 to 2016 and the number is expected to increase or remain high. In response to the issue, the Eleventh Malaysia Plan 2016-2020 was formulated to improve Malaysians’ wellbeing by providing ample open spaces to encourage an active lifestyle. This paper aims to investigate the association of proximity to neighbourhood park and its level of utilisation. 680 respondents were involved in the questionnaire survey conducted at 7 selected neighbourhood parks. The output of the Pearson Correlation evinced that proximity to neeighborhood parks was highly associated to the level of park utilisation. There was a strong and positive relationships between (i) park distance and numbers of visitations (r = 0.841,n = 680,p = 0.000< 0.01), (ii) park distance and length of stay (r = 0.803, n = 680, p = 0.000< 0.01), and (iii) number of visitations and length of stay (r = 0.644, n = 680,p = 0.000< 0.01). The results also indicated that that the longer the distance of the park from home, the longer the time spent at the park. Whereas, the shorter the distance of the park from home, the higher the utilisation of the park.